Homolytic products from heterolytic paths in H2 dissociation on metal oxides: The example of CeO2 - Garcia Melchor, Max (My University, 2014)
Mechanisms for H2 dissociation on metal oxides have been typically inferred from the infrared spectra of reaction products on the basis of the presence or lack of M–H fingerprints. Here, we demonstrate by means of Density Functional Theory that oxides with polar M–O bonds favor heterolytic dissociation. Moreover, we report that the resulting heterolytic product can further evolve to the homolytic one provided that metal ions are reducible. Hence, it follows that the redox capacity of the metal determines the reaction outcome. This finding sheds light on why both M–H and O–H bands appear in the infrared spectra of non-reducible oxides such as MgO or γ-Al2O3, while only O–H bands are observed for reducible oxides like CeO2. It results in a unified mechanism for polar oxides that can be generalized to other materials exhibiting significant charge separation. Importantly, we also show that the low activity of CeO2 towards H2 can be improved by enhancing the basicity of surface O atoms upon lattice expansion. This may pave the way for the efficient use of CeO2 in selective hydrogenation reactions and for the further advance on processes involving dissociation of non-polar bonds like C–H.
PUBLISHED
Keywords: Density Functional Theory; Metal oxides; Ceria; H2 dissociation; Homolytic; Heterolytic